Proteins Specified by Herpes Simplex Virus XI. Identification and Relative Molar Rates of Synthesis of Structural and Nonstructural Herpes Virus Polypeptides in the Infected Cell - Honess, Robert W. (1973)
Analyses of polypeptides made in HEp-2 cells infected with herpes simplex virus type 1 by high-resolution polyacrylamide gel electrophoresis revealed the synthesis of at least 49 infected cell polypeptides (ICP) ranging in molecular weight from 15,000 to 280,000. Evidence for virus specificity based on increased rates of synthesis postinfection, immunological specificity, and viral control of mobility and rate of synthesis was available for 47 of the ICP. These 47 polypeptides can account for 75% of the virus genetic information assuming a DNA molecular weight of 10(8) and asymmetric transcription. On the basis of their mobility relative to virion proteins, the ICP were classified as structural (S, 23 polypeptides), nonstructural (NS, 16 polypeptides), and unassigned (U, 10 polypeptides). Analysis of the synthesis of the ICP revealed the following. (i) Rapid posttranslational cleavages of HSV proteins were not detected; in parallel experiments rapid posttranslational cleavages were readily demonstrated in poliovirus-infected cells and these were blocked by protease inhibitors. (ii) Slow posttranslational changes in the mobility of at least two polypeptides were observed. (iii) Analysis of the rates of synthesis of ICP examined at four intervals postinfection revealed regulation of the pattern and amount of ICP synthesized. ICP formed six classes (A to F) differing in their kinetics of synthesis. S and NS ICP were distributed nonrandomly among these classes. Thus, of the sum of S protein amino acid sequences apportioned among these kinetic classes, 47%, constituting class A and comprising “late” structural proteins, were characterized by progressively increasing rates of synthesis until at least 12 h postinfection; whereas “early” structural proteins constituting class C, amounting to 31% of the total amino acid sequences, were synthesized with initially increasing rates until 4 h postinfection and with declining rates thereafter. NS polypeptides and remaining S polypeptides were distributed among the other kinetic classes—B, D, E, and F. Control of protein abundance was evident in that the polypeptides were not made in equimolar amounts. However, S and NS polypeptides could not be differentiated on the basis of their molar rates of synthesis. The bulk of the detected polypeptides did not differ by more than eightfold in their molar rates of synthesis.